ASSESSMENT OF HYDROCHEMICAL INDICATORS OF DRINKING WATER QUALITY IN SETTLEMENTS WITH NON-CENTRALIZED WATER SUPPLY IN THE AREA OF A MUNICIPAL SOLID WASTE LANDFILL - Kovaleva, Oksana; Drozdova, Natalya (Journal of the Belarusian State University. Ecology, 2026)
The assessment of drinking water quality indicators in the settlements with non-centralized water supply in the areas of potential impact of Gomel landfill was carried out in dynamics. On the basis of quarterly hydrochemical and organoleptic analysis the conformity of drinking water of non-centralized water supply with hygienic safety standards was assessed for 27 indicators. Non-compliance was established for 7 characteristics. Exceedance of MAC of total iron with multiplicity of 2.6-23.6 times in 100 % of samples with maximum content in summer-autumn period was revealed. It is characterized by randomness, weak connection with pollution by other components. Permanganate oxidizability in 44 % of cases exceeded permissible values up to 2.83 times and correlated with the content of total iron in water (r = 0.71). Phosphate content in winter-spring period exceeded MAC 1.3-1.5 times in 50 % of samples. Single samples in summer-autumn period were characterized by exceeding MPC of nitrates up to 1.6 times. The results of seasonal studies of water composition for 2021-2024 revealed the main pollutants of these objects: total iron, nitrates, phosphates, chlorides. A reliable inverse relationship between the content of total iron, sulfates and the distance of sampling objects from the boundaries of the body of the landfill (r = -(0.435-0.88) and r = -0.69, respectively) was established.
Keywords: solid municipal waste landfill; water; non-centralized water supply; hydrochemical and organoleptic indicators